1981
DOI: 10.1073/pnas.78.10.6186
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of a human leukocyte interferon.

Abstract: The primary structures of three major species of human leukocyte. interferon differ from the structure predicted from the DNA sequence of recombinants containing leukocyte interferon-coding regions. Compared to the recombinant interferon produced in bacteria, three of the purified natural proteins isolated from leukocytes lack the 10 COOH-terminal amino acids suggested by the DNA sequence.Although interferon was discovered 23 years ago (1), the structure of the genes and proteins are only now being elucidated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…This suggests that the MPF precursor would fold and then be successively processed with furin-like and trypsin-like proteases. A similar processing has been found in leukocyte-derived natural IFN-a (27) and IFN-g (28,29).…”
Section: Discussionmentioning
confidence: 76%
“…This suggests that the MPF precursor would fold and then be successively processed with furin-like and trypsin-like proteases. A similar processing has been found in leukocyte-derived natural IFN-a (27) and IFN-g (28,29).…”
Section: Discussionmentioning
confidence: 76%
“…Human leukocyte interferon (IFN-a) is a family of individual species differing in amino acid sequences (1)(2)(3). Several recombinant IFN-a molecules and hybrid IFNs have been expressed in Escherichia coli, purified to homogeneity, and characterized (1,(4)(5)(6).…”
mentioning
confidence: 99%
“…Aliquots were then reduced with electrophoresis solubilizing buffer containing 3% 2-mercaptoethanol and applied to 16% polyacrylamide gels containing 0.1% NaDodSO4. ' -- (3,6,19,20). Studies with a monoclonal antibody, which recognizes the last 16 carboxyl-terminal amino acid residues of HuIFN-aA, have confirmed that the carboxyl-terminal region of the HuIFNaA molecule is not involved in interaction with the receptor, for this antibody is capable of binding to HuIFN-aA bound to its receptor (21,22).…”
Section: Resultsmentioning
confidence: 89%